2019
DOI: 10.9734/csji/2019/v26i230086
|View full text |Cite
|
Sign up to set email alerts
|

Cu (II)-Red Onion Skin Extract-Azo metal Complex - A Potential for Oilfield Applications

Abstract: Red Onion skin extract (ROSE)- azo compound of 2-aminophenol and Cu (II) metal complex of the azo compound (Cu-APmROSE) were formed and characterized using FT-IR spectroscopy, UV-Visible absorption spectroscopy and Scanning electron microscopy. The IR Spectra showed the values of N=N- stretching frequency of 1512.24cm-1 at 1500 cm-1 in APmROSE. This stretching frequency is absent in the Cu-APmROSE. This is an indication of the involvement of the N=N- bond in coordination to the metal. APmROSE shows an absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This study adopted two extraction processes: a solvent extraction mechanism [3,23] and cold extraction process [24].…”
Section: Extraction Processmentioning
confidence: 99%
“…This study adopted two extraction processes: a solvent extraction mechanism [3,23] and cold extraction process [24].…”
Section: Extraction Processmentioning
confidence: 99%
“…Research has shown that aromatic azo compounds have the ability to form stable complexes with transition metal due to the presence of the azo groups (-N=N-), oxygen heteroatoms as well as the aromatic rings [12]- [15].A recent study carried out by Akaho and his coworkers showed that red onion skin extract (ROSE) azo compounds can form stable complexes with Cu 2+ ions [16]. This suggests that these azo compounds could be used as low-cost ligands for the extraction of heavy metals such as copper, cobalt, zinc, iron, nickel and many others from aqueous media.…”
Section: Introduction Obalt Ion (Co 2+mentioning
confidence: 99%